SOFT GRAPHS OF THE BARBELL STAR GRAPH - Helmi, Monika Rianti; Sy, Syafrizal; Nazra, Admi; Muhafzan; Hanifa, Nurul; Alfiany, Noverina (Jurnal Matematika UNAND, 2025)
\textit{Let $G^*=(V(G^*),E(G^*))$ is a simple graph and $A$ be a non-empty set of parameter. Let $R\subseteq A× V(G^*)$ be a arbitrary relation from $A$ to $V(G^*)$. A mapping $F:A→ P(V(G^*))$ can be defined as $F(x)=\left\{y\in V\mid xRy \right\}$ and a mapping $K:A→ P(E(G^*))$ can be defined as $K(x)=\left\{uv\in E\mid \left\{u,v\right\}\subseteq F(x)\right\}$. A pair $(F,A)$ and $(K,A)$ are soft sets over $V(G^*)$ and $E(G^*)$ respectively, then $(F(a),K(a))$ is a subgraph of $G^*$. The 4-tuple $G=(G^*,F,K,A)$ is called a soft graph of $G$. In this paper, we enumerate soft graph of amalgamation of path and star.}